Алгоритм розрахунку перехідних і усталених процесів асинхронного мотора - Чабан, Василь Йосипович; Гоголь, Зорана Іванівна; Костючко, Сергій Миколайович (НТУ "ХПІ", 2011)
Запропоновано спільний алгоритм розрахунку перехідних і усталених процесів трифазного асинхронного мотора при наявності конденсатора в одній з фаз статора. Диференціальні рівняння пристрою записані в нормальній формі Коші. Перехідний процес одержується при заданих початкових умовах, усталений - при таких, що виключають перехідну реакцію. Подаються результати симуляції

The paper introduces a calculation algorithm for transient and steady-state processes in a three phase induction motor with a capacitor in one of the stator phases. Differential equations are given in normal Cauchy form. The transient process occurs under given initial conditions, while the steady-state process takes place under such initial conditions that eliminate the transient response. Simulation results are given
A calculation algorithm for transient and steady-state processes in an induction motor
Keywords: форма Коші; симуляція; статор; конденсатор; three phase induction motor; capacitor; transient processes; steady-state processes; simulation